Development of a high-resolution mass-spectrometry-based method and software for human leukocyte antigen typing - Wang, Kun; Sun, Zetao; Zhu, Fei; Xu, Yunping; Zhou, Feng (Frontiers in Immunology, 2023)
Introduction: The human leukocyte antigen (HLA) system plays a critical role in the human immune system and is strongly associated with immune recognition and rejection in organ transplantation. HLA typing method has been extensively studied to increase the success rates of clinical organ transplantation. However, while polymerase chain reaction sequence-based typing (PCR-SBT) remains the gold standard, cis/trans ambiguity and nucleotide sequencing signal overlay during heterozygous typing present a problem. The high cost and low processing speed of Next Generation Sequencing (NGS) also render this approach inadequate for HLA typing. Methods and Materials: To address these limitations of the current HLA typing methods, we developed a novel typing technology based on nucleic acid mass spectrometry (MS) of HLA. Our method takes advantage of the high-resolution mass analysis function of MS and HLAMSTTs (HLA MS Typing Tags, some short fragment PCR amplification target products) with precise primer combinations. Results: We correctly typed HLA by measuring the molecular weights of HLAMSTTs with single nucleotide polymorphisms (SNPs). In addition, we developed a supporting HLA MS typing software to design PCR primers, construct the MS database, and select the best-matching HLA typing results. With this new method, we typed 16 HLA-DQA1 samples, including 6 homozygotes and 10 heterozygotes. The MS typing results were validated by PCR-SBT. Discussion: The MS HLA typing method is rapid, efficient, accurate, and readily applicable to typing of homozygous and heterozygous samples.